The Exopolysaccharide of Xylella fastidiosa Is Essential for Biofilm Formation, Plant Virulence, and Vector Transmission - N. Killiny; R. Hernandez Martinez; C. Korsi Dumenyo; D. A. Cooksey; R. P. P. Almeida (Molecular Plant-Microbe Interactions, 2013)
Exopolysaccharides (EPS) synthesized by plant-pathogenic bacteria are generally essential for virulence. The role of EPS produced by the vector-transmitted bacterium Xylella fastidiosa was investigated by knocking out two genes implicated in the EPS biosynthesis, gumD and gumH. Mutant strains were affected in growth characteristics in vitro, including adhesion to surfaces and biofilm formation. In addition, different assays were used to demonstrate that the mutant strains produced significantly less EPS compared with the wild type. Furthermore, gas chromatography–mass spectrometry showed that both mutant strains did not produce oligosaccharides. Biologically, the mutants were deficient in movement within plants, resulting in an avirulent phenotype. Additionally, mutant strains were affected in transmission by insects: they were very poorly transmitted by and retained within vectors. The gene expression profile indicated upregulation of genes implicated in cell-to-cell signaling and adhesins while downregulation in genes was required for within-plant movement in EPS-deficient strains. These results suggest an essential role for EPS in X. fastidiosa interactions with both plants and insects.